2000
DOI: 10.1074/jbc.275.19.14031
|View full text |Cite
|
Sign up to set email alerts
|

Two Glyceraldehyde-3-phosphate Dehydrogenases with Opposite Physiological Roles in a Nonphotosynthetic Bacterium

Abstract: Bacillus subtilis possesses two similar putative phosphorylating glyceraldehyde-3-phosphate dehydrogenase (GAPDH) encoding genes, gap (renamed gapA) and gapB. A gapA mutant was unable to grow on glycolytic carbon sources, although it developed as well as the wild-type strain on gluconeogenic carbon sources. A gapB mutant showed the opposite phenotype. Purified GapB showed a 50-fold higher GAPDHase activity with NADP ؉ than with NAD ؉ , with K m values of 0.86 and 5.7 mM, respectively. lacZ reporter gene fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
199
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(214 citation statements)
references
References 33 publications
11
199
1
3
Order By: Relevance
“…Two GAPDH encoding genes were identified in the genomes of Methanosarcina species suggesting different metabolic functions. A similar situation is reported in Bacillus subtilis which contains two distinct GAPDHs, one acting in gluconeogenic direction and the other acting in glycolytic direction (Fillinger et al 2000). In order to address if this by-pass is generally found in (hyper)thermophiles the distribution of GAP converting enzymes in (hyper)thermophilic bacteria was studied.…”
Section: -----------------------Mdtkly--idgqwvnsssgktvdkyspvtgqvigrfementioning
confidence: 62%
“…Two GAPDH encoding genes were identified in the genomes of Methanosarcina species suggesting different metabolic functions. A similar situation is reported in Bacillus subtilis which contains two distinct GAPDHs, one acting in gluconeogenic direction and the other acting in glycolytic direction (Fillinger et al 2000). In order to address if this by-pass is generally found in (hyper)thermophiles the distribution of GAP converting enzymes in (hyper)thermophilic bacteria was studied.…”
Section: -----------------------Mdtkly--idgqwvnsssgktvdkyspvtgqvigrfementioning
confidence: 62%
“…127) B. subtilis possesses NADH-and NADPH-dependent glyceraldehyde-3-P dehydrogenases, which are specific for glycolysis and gluconeogenesis and are encoded by gapA and gapB respectively. 131) This protein also represses sr1, 132) which encodes a small non-coding regulatory RNA that inhibits the translation of ahrC encoding a transcriptional regulator that activates the rocABC and rocDEF operons for arginine catabolism and represses the gene cluster for arginine biosynthesis. 108,[133][134][135] CcpN is active when cells are growing on a glycolytic substrate, even if the medium also contains a gluconeogenic substrate.…”
Section: Catabolite Control Mediated By Ccpb Ccpc Ccpn and Cggrmentioning
confidence: 99%
“…In the first phase of gluconeogenesis, pyruvates are converted after several reactions to 1,3-bisphosphoglycerates, which are converted further to GAPs by GAPDH. It has been demonstrated that, in B. subtilis and the cyanobacterium Synechocystis, one of the two GAPDH-encoding gap genes is involved in gluconeogenesis (Fillinger et al, 2000;Koksharova et al, 1998). Our previous work has shown that Xcc strain 8004 possesses a functional gluconeogenesis pathway that is indispensable for the bacterium to utilize pyruvate as the sole carbon source .…”
Section: Discussionmentioning
confidence: 99%
“…Data are the means±SD from three replicates. Fillinger et al, 2000;Koksharova et al, 1998). In many bacteria, glucose is catabolized through the glycolysis pathway, which functions primarily to provide energy in the form of ATP (Gottschalk, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation